Primary central nervous system lymphoma in daily practice and the role of autologous stem cell transplantation in relapsed disease: A retrospective multicenter study. Issue 1 (February 2016) - Erkurt, Mehmet Ali; Berber, Ilhami; Tekgündüz, Emre; Dogu, Mehmet Hilmi; Korkmaz, Serdal; Demir, Cengiz; Yilmaz, Mehmet; Akay, Olga Meltem; Pala, Ciğdem; Bilen, Yusuf; Kaya, Emin; Sari, Ismail; et al.
Abstract: We investigated the course of 54 patients presenting with primary central nervous system lymphoma, who were treated in daily practice. The patients were treated with chemotherapy and/or radiotherapy and/or intrathecal chemotherapy. At a median follow-up period of 23 months (range 1–71), median relapse-free survival (RFS) and overall survival (OS) were not reached. Estimated 2-year RFS and OS rates were 42% and 48%, respectively. Ten relapsed PCNSL patients underwent ASCT. Complete remission rate of these patients was 40%, with 20% treatment-related mortality. Estimated 2-year RFS and OS rates were 37% and 40%, respectively. The prognosis of patients with PCNSL, who received off-study treatment, is still dismal.